Left atrial appendage occlusion in chicken‐wing anatomies: Imaging assessment, procedural, and clinical outcomes of the "sandwich technique". Issue 7 (13th February 2021) - Freixa, Xavier; Tzikas, Apostolos; Aminian, Adel; Flores‐Umanzor, Eduardo; De Backer, Ole; Korsholm, Kasper; Ben Yedder, Mohamed; Gonzalez‐Ferreiro, Rocío; Agudelo‐Montañez, Victor; Gilhofer, Thomas; Simon, François; Samaras, Athanasios; et al.
Abstract: Objectives: To describe imaging assessment, procedural and follow‐up outcome of patients undergoing left atrial appendage (LAA) occlusion (LAAO) using a "sandwich" technique. Background: The presence of a LAA with chicken wing morphology constitutes a challenge that sometimes requires specific occlusion strategies like the "sandwich" technique. However, procedural and follow‐up data focusing on this implanting strategy is scarce. Methods: This multicenter study collected individual data from eight centers between 2012 and 2019. Consecutive patients with chicken‐wing LAAs defined as an early (<20 mm from the ostium) and severe bend (>90°) who underwent LAAO with Amplatzer devices and using the "sandwich" technique were included in the analysis. Results: Overall, 190 subjects were enrolled in the study. Procedures were done with the Amulet device (85%) and the Amplatzer Cardiac Plug (15%). Successful implantation was achieved in 99.5% with ≤1 partial recapture in 80% of cases. Single (46.2%) and dual antiplatelet therapy (39.4%) were the most used antithrombotic therapies after LAAO. In‐hospital major adverse events rate was 1.5% with no deaths. One patient (0.5%) had cardiac tamponade requiring percutaneous drainage. With a mean follow‐up of 19.6 ± 14.8 months, the mortality and stroke rates were 7.7%/year and 2.5%/year, respectively. Follow‐up transesophageal echocardiography (TEE) at 2–3 months showed device‐related thrombosis in 2.8% and peri‐device leak ≥3 mm in 1.2% of patients. Conclusions: In a large series of patients with chicken wing LAA anatomies undergoing LAAO, the use of the "sandwich" technique was feasible and safe. Preprocedural imaging was a key‐factor to determine specific measurements.